Pengaruh Konsentrasi Mikoriza Terhadap Pertumbuhan Dan Hasil Tanaman Kangkung Darat (Ipomea reptans Poir) - Novianto (Indoensia), Esna Dilli; Laeshita (Indoensia), Putri; Nuswantoro (Indoensia), Gumilar Tejo (Universitas Tidar, 2023)
A fungus called mycorrhiza may coexist harmoniously with plants. The goal of this study is to ascertain how five different mycorrhizal concentrations affect the yield and growth of ground kale.The five-block, completely randomized block design (RAKL), non-factorial experiment that was used for this study was carried out from May to June 2022. In terms of plant height, number of branches, fresh weight consumed, dried weight consumed, and root length, the results showed that the usage of five mycorrhizal concentrations did not significantly differ, but there was a considerable difference in the number of leaves produced by each plant. Giving mycorrhizal concentrations could enhance the number of leaves on water spinach, but it could not improve plant height, number of branches, fresh weight for consumption, dried weight for consumption, or root length (Ipomea reptans Poir).Keywords Kale (Ipomea reptans Poir), mycorrhizal, growth